2021
DOI: 10.3390/plants10071481
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CRISPR/Cas-Mediated Targeted Mutagenesis in Spring and Winter Wheat Varieties

Abstract: CRISPR/Cas technology has recently become the molecular tool of choice for gene function studies in plants as well as crop improvement. Wheat is a globally important staple crop with a well annotated genome and there is plenty of scope for improving its agriculturally important traits using genome editing technologies, such as CRISPR/Cas. As part of this study we targeted three different genes in hexaploid wheat Triticum aestivum: TaBAK1-2 in the spring cultivar Cadenza as well as Ta-eIF4E and Ta-eIF(iso)4E in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In cucumbers, knocking out the eIF4E gene using the CRISPR/Cas9 system resulted in broad-spectrum resistance to members of the Potyviridae family, including cucumber vein yellowing virus, papaya ringspot virus, and zucchini yellow mosaic virus (Chandrasekaran et al 2016). In wheat, TaeIF(iso)4e-mutant lines were obtained using CRISPR-Cas9 genome-editing technology, which revealed that the corresponding mutations can potentially confer WSSMV and WYMV resistance (Hahn et al 2021). Recently, the wheat orthologs of the barley susceptibility factor disulfide isomerase like 5-1 (HvPDIL5-1) were edited in the wheat genome, conferring WYMV resistance in wheat (Kan et al 2022).…”
Section: Disease Managementmentioning
confidence: 99%
“…In cucumbers, knocking out the eIF4E gene using the CRISPR/Cas9 system resulted in broad-spectrum resistance to members of the Potyviridae family, including cucumber vein yellowing virus, papaya ringspot virus, and zucchini yellow mosaic virus (Chandrasekaran et al 2016). In wheat, TaeIF(iso)4e-mutant lines were obtained using CRISPR-Cas9 genome-editing technology, which revealed that the corresponding mutations can potentially confer WSSMV and WYMV resistance (Hahn et al 2021). Recently, the wheat orthologs of the barley susceptibility factor disulfide isomerase like 5-1 (HvPDIL5-1) were edited in the wheat genome, conferring WYMV resistance in wheat (Kan et al 2022).…”
Section: Disease Managementmentioning
confidence: 99%
“…CRISPR-Cas is one of the key methods employed by many molecular biology scientific laboratories. Since its first description [14], genome editing focused research was implemented by countless research groups [15][16][17].…”
Section: The Crispr-cas Systemmentioning
confidence: 99%